Kesadaran remaja dalam mengenali jenis dan dampak narkotika dan psikotropika - Hamsu Abdul Gani; Andika Wahyudi Gani (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Narcotics and psychotropic drugs or substances that are useful in the fields of medicine, health services, and scientificdevelopment, but on the other hand the use of narcotics and psychotropic substances can also cause a very detrimentaldependency if used without control, strict and careful supervision. Drug abuse at the end of this year is felt to be increasing.Based on the statistics of the SUL-SEL BNN report from the number of dealers and dealers in 2016, there were 12,423 people.And in 2017, there was an increase of 19,514 people. Then from the number of users in 2016 as many as 15,869 people and in2017 again experienced an increase of 21,961 users and finally in 2018 SUL-SEL received the title as the 7th ranking of the mostnarcotics users in Indonesia.